Government Process Reengineering in the Implementation of Electronic Welfare System - Intan Kusuma Dewayani; Rino A. Nugroho (Spirit Publik: Jurnal Administrasi Publik, 2021)
In the current era of globalization, it cannot be denied that the presence of technology is certainly very helpful for human work. In the level of government, technological developments have also been exploited by bringing up electronic government. In utilizing the development of existing technology, the Surakarta City Government through the Surakarta City Social Service is trying to make a new breakthrough by creating an Sistem Informasi Kesejahteraan Elektronik (E-SIK) which is expected to be used to overcome the problem of the data of poor families in the city of Surakarta, because there are findings stating that the data of poor families in the city of Surakarta that entered in the last two years turned out to be almost thirty percent of the indicators received or produced incomplete, so that the data could not be processed. It should be recalled, that one of the basics and prerequisites for implementation e-government is the Government Business Process Reengineering, but the Government Process Reengineering is not enough to fix functional and non-functional problems. the methodological procedures that will be used are forecasting, the forecasting approach extrapolation or ekstrapolative forecasting. It will begin by reviewing a series of data or previous research documents with similar research objects and research problems, namely regarding obstacles in the process of implementing e-government in various regions, then trying to project them with research that will be carried out to predict the possibility. obstacles that will arise during the process of implementing an Electronic Welfare Information System (E-SIK).